2021
DOI: 10.1038/s41598-021-00169-x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of genetic modifiers of hemoglobinopathies leading towards precision medicine

Abstract: Hemoglobinopathies though a monogenic disorder, show phenotypic variability. Hence, understanding the genetics underlying the heritable sub-phenotypes of hemoglobinopathies, specific to each population, would be prognostically useful and could inform personalized therapeutics. This study aimed to evaluate the role of genetic modifiers leading to higher HbF production with cumulative impact of the modifiers on disease severity. 200 patients (100 β-thalassemia homozygotes, 100 Sickle Cell Anemia), and 50 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
4
3
0
1
Order By: Relevance
“…Hariharan P et al in their study also reported 3 bp deletional allele of rs66650371 to be significantly associated with higher HbF levels in SCA. Similar findings were reported in our study 15 . In the promoter region of G γ globin, the XmnI polymorphism residing in the − 158 (C → T) was detected in our SCD patient group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hariharan P et al in their study also reported 3 bp deletional allele of rs66650371 to be significantly associated with higher HbF levels in SCA. Similar findings were reported in our study 15 . In the promoter region of G γ globin, the XmnI polymorphism residing in the − 158 (C → T) was detected in our SCD patient group.…”
Section: Discussionsupporting
confidence: 93%
“…The mutant T allele was significantly associated with raised HbF levels in patients. Similar to our findings Hariharan P et al, 2021 also reported 94% homozygosity for mutant T allele in SCD patient group 15 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar ndings were reported in our study [31]. In the promoter region of G γ globin, the XmnI polymorphism residing in the − 158 (C → T) was detected in our SCD patient group.…”
Section: Discussionsupporting
confidence: 92%
“…The mutant T allele was signi cantly associated with raised HbF levels in patients. Similar to our ndings Hariharan P et al, 2021 also reported 94% homozygosity for mutant T allele in SCD patient group [31].…”
Section: Discussionsupporting
confidence: 92%